Characterization of patients with bacterial infections associated with hemodialysis catheters - Pascual De Jesús López Escudero; Zurelis Pompa Gutiérrez; Betsy Álvarez Vázquez (Revista Cubana de Medicina Militar)
Introduction: Catheter-associated infection is the most frequent septic complication in patients with chronic renal failure on hemodialysis. Objective: Characterize patients with end-stage chronic kidney disease, with bacterial infections associated with the use of a catheter for hemodialysis. Methods: A descriptive, observational, cross-sectional study was conducted between January 2016 and December 2017. The universe consisted of the total number of patients (83) with bacterial infection. The variables studied included the form of presentation of sepsis, age, sex, etiology of chronic renal failure, complications, symptoms, signs and most frequently isolated germs. Absolute frequencies and percentages were used as summary measures; mean, median and mode were also used. Results: 90.36% of the patients presented bacteremia and 9.64% infection of the catheter insertion site. Male sex and renal failure secondary to diabetes mellitus predominated, with 49.39 %. The mean age was 65.84 years. Prevalent symptoms and signs were tremor, shivering and decay. Loss of vascular access was the most frequent complication (43.37%). Staphylococcus aureus was isolated in 86.75 % of cases. Conclusions: Most of the patients presented bacteremia, male sex predominated, and renal failure secondary to diabetes mellitus. The mean age was over 65 years. The most frequent symptoms and signs were, tremor, chills and decay. Loss of vascular access was the most frequent complication. Staphylococcus aureus was isolated in more than 85% of the cases.